Pengaruh Media Audio-Visual Canva terhadap Peningkatan Kemampuan Membaca Siswa Disleksia di SDN 2 Sukamulya - adisyanurfadillah; Erna; Anisa; Wini; Jihan; Lia; Ridho; Reka; Aulia; Rifqi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
In education, reading ability is a very important basic skill. However, not all students are able to master reading skills well, especially students who have dyslexia. Based on initial observations at SD Negeri 2 Sukamulya, it was found that several students had difficulty recognizing letters, arranging letters into words, and reading fluently, thus hampering the learning process. Therefore, learning media is needed that suits the characteristics of dyslexic students, one of which is through the use of Canva-based audio-visual media. This research aims to determine the characteristics of dyslexic students, describe the application of Canva audio-visual media, and analyze the effect of its use on improving the reading ability of dyslexic students at SD Negeri 2 Sukamulya. This research uses a quantitative approach with a pre-experimental method and a One Group Pretest–Posttest design. The research subjects were five dyslexic students who were selected using purposive sampling techniques. Data collection was carried out through reading and observation tests, while data analysis used normality tests and hypothesis testing in the form of paired sample t-test. The results of the research showed that there was an increase in students' reading abilities after being given treatment using Canva audio-visual media. The average pretest score of 38 increased to 52 on the posttest. The results of the hypothesis test show a significance value (Sig. 2-tailed) of 0.033 < 0.05. Thus, it can be concluded that the use of Canva-based audio-visual media has a significant effect on improving the reading ability of dyslexic students at SD Negeri 2 Sukamulya.